2015
DOI: 10.1111/jopr.12387
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Surface Treatments on Porcelain‐Resin Bond Strength

Abstract: Silanization after coating with silica improves the bond strengths of both EX and ICZ specimens, while HF etching is favorable only for the EX specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 37 publications
3
32
0
Order By: Relevance
“…Another study also corroborated these finding and noted that conditioning the PEEK surface with MMA‐containing adhesive systems after silica coating or sandblasting increased the SBS values . Stawarczyk et al noted that Visio.link acted as the positive control group, because all previous studies showed very high bonding properties after the use of Visio.link as conditioner on different pretreated PEEK surfaces, and recommended sandblasting as one of the best initial pretreatment options for PEEK surfaces . Thus, the current findings are not surprising.…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…Another study also corroborated these finding and noted that conditioning the PEEK surface with MMA‐containing adhesive systems after silica coating or sandblasting increased the SBS values . Stawarczyk et al noted that Visio.link acted as the positive control group, because all previous studies showed very high bonding properties after the use of Visio.link as conditioner on different pretreated PEEK surfaces, and recommended sandblasting as one of the best initial pretreatment options for PEEK surfaces . Thus, the current findings are not surprising.…”
Section: Discussionsupporting
confidence: 81%
“…Laser energy was applied to the surface with a noncontact handpiece (H02‐N, 0.9 mm spot size), and the laser beam was aligned perpendicular to the specimen surface at a distance of 10 mm. The entire surface of the specimen was scanned manually with the laser beam while being cooled with water and air . After pretreatments, all specimens were cleaned with the distilled water in an ultrasonic cleaner for 60 seconds and dried with oil‐free air.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations